2021
DOI: 10.1093/cid/ciab246
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Low Prevalence of Schistosoma mansoni: Modeling the Effect of Less Frequent Treatment

Abstract: Background The World Health Organization (WHO) previously set goals of controlling morbidity due to schistosomiasis by 2020 and attaining elimination as a public health problem (EPHP) by 2025 (now adjusted to 2030 in the new neglected tropical diseases roadmap). As these milestones are reached, it is important that programs reassess their treatment strategies to either maintain these goals or progress from morbidity control to EPHP and ultimately to interruption of transmission. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Previous mathematical work [ 13 ] has shown that it is possible to achieve and sustain the EPHP goal by adopting various MDA treatment strategies. The probability of achieving and maintaining this goal depends on the baseline prevalence prior to treatment, the precise form of the age–intensity profile of infection and the strategy adopted in terms of MDA coverage and treatment frequency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous mathematical work [ 13 ] has shown that it is possible to achieve and sustain the EPHP goal by adopting various MDA treatment strategies. The probability of achieving and maintaining this goal depends on the baseline prevalence prior to treatment, the precise form of the age–intensity profile of infection and the strategy adopted in terms of MDA coverage and treatment frequency.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work [ 13 ], we have explored the strategies in the design of MDA programmes needed to be adopted to achieve and sustain the elimination of schistosomiasis as a public health problem. This past work has focused on the MDA coverage required across all child and adult age groups to achieve specified targets by a defined year.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is common for adults to exhibit greater morbidity, but lower egg counts, than children, likely from long-lasting, untreated chronic infections (29). Models have recently shown that in some settings, reaching these morbidity targets and reactively reducing treatment frequency could result in recrudescence (30). suggesting the morbidity targets are not an optimal stepping stone and that the reduction of prevalence as suggested elsewhere (31) will be more effective.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, once the targets are reached, there remain uncertainties about how feasible it will be to maintain low prevalence levels in some areas without continued rounds of PC, potentially in perpetuity. 12 This perpetuation of biomedical solutions to complex infectious disease problems delivered through vertical programmes, despite evidence favouring more holistic approaches, has been well documented and critiqued. 13 14 These interventions have been largely devised outside of the recipient localities and are often implemented without the genuine input from relevant public authorities and intended beneficiaries.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…The inclusion of additional interventions, such as snail (vector) management and water sanitation and hygiene (WASH) activities, has been predicted to reach the targets within the time frame specified in the NTD Road Map to 2030,9 yet remain as secondary or optional components to the MDA-focused agendas of many donors, policymakers and researchers. In addition, once the targets are reached, there remain uncertainties about how feasible it will be to maintain low prevalence levels in some areas without continued rounds of PC, potentially in perpetuity 12…”
Section: Introductionmentioning
confidence: 99%